Education Financing and Public-private Partnership Development Assistance Model. (22nd April 2015) - Kim, Jasper; Han, Michelle
Abstract: This article argues for the greater use of "public-private partnerships" (PPP) and "social impact bonds" (SIBs) that innovatively incorporate both the private and public sector to fund a specified education project for social good. In a PPP-SIB structure, a "success metric" is agreed upon prior to issuance by all related parties. This PPP funding model differs from traditional education bond funding, whereby the government would be entirely responsible for repaying the issued bond's principal and interest. In short, the use of SIBs and the PPP education-funding model to complement (but not replace) other sources of education financing could help resolve some of the budgetary capital constraints that currently exist, whereby such capital constraints tangibly hamper educational productivity and performance.